PERANAN MULTIKULTURALISME DALAM ISLAM - Ari Laso; Sri Rahayu; Nadiya (CV Putra Publisher, 2022)
Indonesia, as a country with high cultural and religious diversity, faces challenges in maintaining social harmony amidst differences. This study aims to explore the role of multiculturalism and religion, especially Islam, in shaping national and state life. The method used is qualitative with a literature review approach, which allows researchers to collect, analyze, and synthesize various literatures relevant to the research topic. Data sources were obtained from secondary literature including scientific journals, books, research reports, and policy documents. Literature searches were carried out systematically using keywords such as